The Role of Islamic Communication in Responding to the Human Rights Issues in Indonesia - Hamdan Hamdan (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2020)
This article aims to describe the role of Islamic communication in addressing human rights issues especially in Indonesia. The problems are explained in a descriptive qualitative method by exploring the Islamic conception of human rights and the role of Islamic communication in upholding it. The results showed that Islam has a teaching respect for human rights that can be explored from various sources of Islamic teachings. Thus, Muslims must be proactive people of encouraging the growth of awareness of human rights. In this context, Islamic communication gets its urgency. The da'i, both institutionally and individually, must have the ability to become expert in understanding the human rights issues. Muslims must be actively involved in today’s world, so that they should be the important part and contribute positively in order to make the Islamic campaign as rahmatan li al-'alamin